Three‐Dimensional Transesophageal Echocardiography Assessment of a Successful Transcatheter Mitral Valve in Valve Implantation for Degenerated Bioprosthesis. Issue 6 (12th March 2013) - Théron, Alexis; Gariboldi, Vlad; Grisoli, Dominique; Maysou, Laurie‐anne; Jaussaud, Nicolas; Morera, Pierre; Cuisset, Thomas; Quilici, Jacques; Thuny, Franck; Riberi, Alberto; Avierinos, Jean‐François; Collart, Frederic
<x xml:space="preserve">Abstract</x> Reoperation for degenerated mitral bioprosthesis is considered a high risk procedure. Transcatheter mitral valve in valve implantation has emerged as an off‐label alternative for patients contra‐indicated to surgery. We report a 46‐year‐old man, with a 29 mm mitral bioprosthesis since 2002, who was admitted for acute heart failure because of a severe intra‐prosthetic regurgitation. His recent medical history revealed a fast growing cavum carcinoma. In view of generally poor prognosis, the heart team decided to perform a transcatheter mitral valve in valve implantation by transapical approach. Live three‐dimensional TEE was used during the implantation for sizing, device positioning, and hemodynamic assessment.